2009
DOI: 10.1128/cvi.00210-08
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Particle Endocytosis by Epithelial Cells Is Selective and Enhanced by Tumor Necrosis Factor Receptor Ligands

Abstract: Bacterial pathogens use virulence strategies to invade epithelial barriers, but active processes of epithelial cells may also contribute to the endocytosis of microbial particles. To focus on the latter, we studied the uptake of fixed and fluorescently labeled bacterial particles in intestinal and bronchoepithelial cell cultures and found it to be enhanced in Caco-2BBe and NCI-H292 cells after treatment with tumor necrosis factor alpha and an agonist antibody against the lymphotoxin beta receptor. Confocal flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…These changes were also associated with a functional increase in the endocytosis of bacterial particles, as shown by the Staphylococcus aureus endocytosed by the cytokine-treated Caco-2BBe cells (Figure 4b). This effect has also been described in more quantitative studies [42]. …”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…These changes were also associated with a functional increase in the endocytosis of bacterial particles, as shown by the Staphylococcus aureus endocytosed by the cytokine-treated Caco-2BBe cells (Figure 4b). This effect has also been described in more quantitative studies [42]. …”
Section: Resultssupporting
confidence: 70%
“…We recently reported that the same cytokine treatment of airway and intestinal epithelial cells also increased their capacity to endocytose bacterial particles [42], and in some cases Claudin-4 was associated with the endocytosis vesicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytoplasmic vesicles with CD137 did not co-localize with the tight junction protein Claudin 4, a protein that we previously reported to be associated with particle endocytosis in cytokinetreated cells. 17,31 However, we did find that most of the cytoplasmic CD137 co-localized with the extracellular matrix protein fibronectin (Figure 1), though it was not associated with fibronectin at the surface of the cells. The cytoplasmic associations may also account for the apparent decrease in cell-associated fibronectin in the cytokine treated cells; this pattern suggests that fibronectin synthesized by the epithelial cells was endocytosed in association with CD137 either during synthesis or soon after both proteins appeared at the surface of the cells.…”
Section: Tnf/lymphotoxin Signals and Induction Of Cd137 In Intestinalmentioning
confidence: 70%
“…The gut is the first line of defense against endotoxin and, if cornpromised via nutrition, stress or rnetabolic state, endotoxin transport can increase (Suganuma et al, 2002;Clark et al, 2009;Liu et al, 2009). A greater understanding of gut endotoxin transport ( Figure 2) will allow for the development of nutritional and pharmacological mitigation strategies to avert the negative effects of endotoxin and improve production efficiencies in livestock.…”
Section: Endotoxin Signaling and Transportmentioning
confidence: 98%